Implementasi Manajemen Strategik Dalam Meningkatkan Mutu Pendidikan Di Madrasah Aliyah Negeri 1 Banyuwangi Tahun Pembelajaran 2018/2019 - Aimah, Siti; Quswa, Ana Ghoyatul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2019)
The objectives set in this study are: (1) To find out how the implementation of strategic management in MAN 1 Banyuwangi in the 2018/2019 academic year; (2) To find out how the quality of education in MAN 1 Banyuwangi in the 2018/2019 study year; (3) To find out what factors can improve the quality of education in MAN 1 Banyuwangi; (4) To find out how the right strategy is applied in improving the quality of education in MAN 1 Banyuwangi. This research method uses descriptive qualitative, data collection through interviews, observation, and documentation. Data analysis using SWOT analysis and interactive three models, while the data validity techniques using triangulation. The results of his research: Implementation of Strategy in MAN 1 Banyuwangi: Implementation of activities involves internal and external stakeholders so as to create a sense of kinship, evaluation in accordance with the basic competencies of all subjects so that 87% MAN 1 Banyuwangi output is widely accepted in several Indonesian PTNs. While developing the quality of education: Selective in recruiting students, the existence of Sarpras Innovations outside SNP Improvement of human resource educators and education personnel with training by the Ministry of Religion. The strategy was formulated to improve the quality of education in MAN 1 Banyuwangi: There is a need for the totality of madrasa managers in fostering self-awareness of educators and educators in every activity that is nuanced in a religious environment.